Effect of Occupational Exposure to Cyanuric Chloride on Respiratory Morbidity: Cross-Sectional Analyses of Respiratory Symptoms and Longitudinal Analyses of Lung Function Parameters. Issue 1 (January 2019) - Morfeld, Peter; Yong, Mei
Abstract : Objective: The study aimed to investigate the relationship between occupational exposure to cyanuric chloride and respiratory morbidity. Methods: The cohort comprises former and active workers at three European production sites. Individual cumulative exposure, exposure duration, and long-term average concentration were estimated. In the longitudinal analyses, generalized equation estimates (GEEs) models were used to estimate the risks. To determine a threshold value for cumulative exposure, hockey-stick models were fitted. Results: A sensitization to cyanuric chloride, without an effect on lung function, has been observed. For the total cohort, both the single models and the multimodel analyses provided hints of lung function loss resulting from long-term exposure to cyanuric chloride. With respect to the estimated average loss from a representative model, a cumulative exposure of 0.3 mg/m 3 -years (0.2 to 0.4 mg/m 3 -years) yielded the best model fit. Conclusion: A shift reference value (time-weighted average, 8 hours) of 0.06 mg/m 3 could be derived. For future research, a larger database of exposure measurements and continuing health monitoring will be valuable.